RELEVANSI PEMIKIRAN PENDIDIKAN MUKTI ALI DALAM PENDIDIKAN INDONESIA ERA MILENIUM - Nashir Wahid (Institut Islam Mamba'ul 'Ulum Surakarta, 2021)
Mukti Ali's thoughts can provide new enthusiasm for re-examining Indonesia's educational goals now. The idea of education of Mukti Ali has given color to the concept of education in Indonesia. This can be seen by the revision of the concept of the Indonesian education curriculum into the 2013 curriculum. The 2013 curriculum simply wants to integrate various values of education in learning. The focus of this paper discusses who Mukti Ali is in education and how the concepts and relevance of Mukti Ali's education to Indonesia in the millennium era. To support the writing, the writer traced through several sources, namely through the original book by Mukti Ali and related supporting sources. The results of this paper explain that the concept of Mukti Ali's educational thinking is based on scientific concepts, national concepts, and humanitarian concepts. With these three focuses of thought, Mukti Ali seeks to develop civilization and education through the results of the Decree of the 3 Ministerial Decree, namely the existence of the same degree of graduates of public schools and madrasas. This means that Mukti Ali has initiated the concept of non-dichotomic education, the integration of educational values between religion, humans, and society. Whereas further the concept of Mukti Ali's education has been implemented by basic education institutions (SD / MI, SMP / MTs), secondary and vocational (high school, high school / MA, MAK) and higher education both private and public in Indonesia.